Nilai-Nilai Pendidikan Budi Pekerti dalam Buku Teks Mata Pelajaran Sejarah Kebudayaan Islam - Alrita Mulyaningsih; hakiman hakiman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
In the 2013 curriculum, character education is integrated into the subject book by including it in Core Competencies (KI) 1 and 2, religious attitudes and social attitudes. The textbook of Islamic Cultural History (SKI) is one of the books mandated to contain these competencies. Through the stories of the life journey of Rasullulah and his friends, as well as figures who colored the development of the Islamic world, it is hoped that students can take worship and can emulate the attitudes and characteristics of Rasullulah. The purpose of this study was to describe the values of character education in Islamic Culture History Subject Texbooks for class X Madrasah Aliyah odd Semesters. This study uses literature research with a descriptive approach. The values of character education contained in the textbook of Islamic Cultural History class X MA in the odd semester include religious values, nationalist values, independence values, integrity values, and mutual cooperation values